SYNTHESIS, CHARACTERIZATION, ANTIOXIDANT ACTIVITY OF COPPER(II) GALLATE AND MANGANESE(II)-GALLATE COMPLEXES - Yusup Faisal, Fahmi
Many researchers have carried out the synthesis of complex compounds using phenolic group ligands, with the aim of increasing the solubility of these phenolic compounds. One of the phenolic compounds that has been used for synthesis with metal ions is gallic acid (3,4,5-trihydroxybenzoic acid, C7H6O5). Several complex compounds with gallic acid ligands that have been synthesized include complexes with the metal ions Fe(III), Mn(II), Co(II), Cu(II), and Zn(II). Information regarding the solubility of these complexes is still limited. Therefore, this research has been carried out using a complex synthesis strategy of Cu(II)-Gallate and Mn(II)-Gallate using the microwave method, to obtain complex compounds that can dissolve in air. This was done to study the potential of these two complex compounds as antioxidants in vitro. The strategy used in this research is to convert gallic acid into sodium gallate salt first, so that the pH of the solution is relatively consistent during the complex synthesis. The synthesized complex underwent several characterizations, including solubility tests, CHNS (Carbon, Hydrogen, Nitrogen, Sulfur) element analysis, Atomic Absorption Spectrophotometry (AAS), magnetic susceptibility, powder X-ray diffraction (P-XRD), infrared (FTIR) and UV-Vis spectrophotometry, and Cyclic Voltammetry (CV). From the results of CHNS elemental analysis and AAS, the complex obtained in the research has the molecular formulas CuC7H8O7 and MnC7H8O7. Both complex compounds dissolve well in water. The results of powder X-ray diffraction (P-XRD) measurements show that the diffractogram of the synthesized Mn(II)-Gallate complex is in accordance with the published single crystal diffractogram (SC-XRD). Both complex compounds are paramagnetic with a magnetic moment of 1.78 BM for CuC7H8O7 and 5.93 BM for MnC7H8O7. The coordination bond between Cu(II) or Mn(II) ions and gallate ions is shown in the fingerprint region of the infrared spectrum, namely at wavenumbers 503 cm-1 for Cu-O and 573 cm-1 for Mn-O. In addition, there are changes in the number of waves of the carboxyl and hydroxyl functional groups of the gallate ion. The stretch of the O-H group shifted from 3213 cm-1 to 3431 cm-1 for the Cu(II)-Gallate complex and 3406 cm-1 for the Mn(II)-Gallate complex. Meanwhile, the strain of the C=O group shifts from a wavenumber of 1561 cm-1 to 1627 cm-1 for the Cu(II)-Gallate complex and 1602 cm-1 for the Mn(II)-Gallate complex. The results of the antioxidant test using DPPH reagent obtained an IC50 value for the Cu(II)-Gallate complex is 2.59 mM, and for the Mn(II)-Gallate complex is 2.40 mM. Furthermore, the results of cyclic voltammetry (CV) measurements show that the two complexes have redox potential values that lie in the range of potential for the oxidation of DPPH• radicals (0.006 V vs. NHE) and potential for their reduction (0.806 V vs. NHE). Based on these CV measurements, both complexes have the potential to capture DPPH• radicals, through the reduction reaction of DPPH• radical anions into more stable DPPH molecules.